Pengaruh Mutu Proses Stockfit Terhadap Hasil Uji Bonding Bottom Sepatu Running dengan Metode Cementing di Perusahaan Sepatu Olah Raga Karawang-Jawa Barat - Vivi Winda Sari; Diana Ross Arief; Cahya Widiyati (Politeknik ATK Yogyakarta, 2017)
Quality control is conducted to minimize the reject of production. Quality of bottom is one of the important factors in making shoes. The bottom quality standards are determined based on the strength of glue adhesion between the components. The study was held at one of sport shoe companies from 13th March to 13th April 2017 with the purpose to reveal the quality control of the stockfit process to the test results of running shoes bonding bottom with cementing method. The stockfit process consists of few steps, for instance outsole buffing, outsole trimming, setting bottom, primering, cementing, attaching, pressing, press pong-pong, and cooling. Finished products were tested in the laboratory by random sampling. The quality control of running-shoe bottom stockfit process uses Plan-Do-Check-Action (PDCA) method in each process and is continued by analyzing the result of bonding test by adapting quality control tools. The result of the analysis shows the cause of failure of bonding or reject due to less perfect glue adhesiveness between midsole / outsole by 71,11%, midsole / midsole2 3,33%, midsole1,2 / gel outside 3,33%, midsole1,3 / gel heel back of 18.89%, and midsole/shank is 3.33%. Quality control at this company has been well implemented.